Reconnnaissance survey of the soils of Rio Grande do Sul State, Brazil - Lemos, Raimundo Costa de; Azolin, Miguel Ângelo Décimo; Abrão, Paulo Ubirajara Rodrigues; Santos, Milton da Conceição Lopes dos; Carvalho, Américo Pereira de (Pesquisa Agropecuaria Brasileira, 2014)
The reconnaissance survey of the soils of Rio Grande do Sul State has been underway since 1961. It represents another step toward the delineation of the Brazilian Soil Map, an important and useful device for a general inventory of potential resources of the soils of Brazilian Territory. The purpose of this survey is to define and delimit the most important soil units of RGS State, providing for basic research. The area of RGS State is approximately 280.000 km2, of which 80.000 km2 has been mapped. This survey was made possible through the use of municipal maps is scales of 1:50.000 and 1:100.000, of a general map of RGS State in scale of 1:750.000, aerophotos covering parts of the area, and of “quadriculas” from “Conselho Nacional de Geografia” in the scale of 1:500.000. The work was done using the direct measurement method. Aerophotos were available only for such a municipalities as Santo Angelo, Guarany das Missões, and sections of Cruz Alta, Ijuí, Cerro Largo, São Luiz Conzaga, Catuipe and Giruá (Fig. 1).